Toni Morrison’s Beloved: A Study on History, Slavery and Love (Pursuits: A Journal of English Studies, 2022)
This article makes an effort to describe Toni Morrison’s novel, Beloved as a fusion of History, slavery and love. It also reveals that history of Afro-Americans, slave narrative; love and fantasy are the main assets of the novel. In the novel, she focuses on the horror of the past so that Afro-Americans and the Americans all those who involved with slavery would come face to face with grim reality of the past and rise above it. The novel articulates and embodies a history of slavery of African-Americans and their experiences, which has been apparently, accurately and carefully recovered but is actually uncooked. Beloved directly confronts racism which combines lyrical beauty with an assault on the readers’ emotions and conscience. It emphasizes the legacy of slavery using forms resulting from traditional Back Folk aesthetic. It deals with the life and history of Black American women immediately after the emancipation of slaves in the North. Beloved also presents a tragedy involving mother’s moment of choice, and a love story exploring what it means to be beloved. Thus the novel holds the key to the narrative’s unity. The subject matter is stressful to read and it is also confrontational and painful. The form combines historical realism with magic, slavery and love.